A mini review on the methods for the extraction, isolation, and determination of P. odorata's bioactive compounds / Nur Ain Syabila Kiraman and Hartini Yusof - Kiraman, Nur Ain Syabila; Yusof, Hartini (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Persicaria odorata is a perennial herb of the Persicaria genus, which belongs to the Polygonaceae family.P. odorata is commonly known in Malaysia as daun kesum and is widely used in cuisine and has different medicinal benefits. The medicinal benefits from P. odorata are contributed by its various bioactive compounds and biological activities. Thus, phytochemical analysis has been researched extensively to maximize the benefits of the plant. For herbal studies, extraction plays a crucial step in extracting the preferred bioactive compounds hence several extraction techniques such as chromatography, electrophoresis, and spectroscopy have been developed to separate and identify bioactive compounds. In turn, these compounds play a big role on the biological activities of the plant. This review highlights the methods for extraction, separation, and identification of bioactive compounds and the biological activities of P. odorata.